DIDACTICA DE LA MATEMATICAY SU INCIDENCIA EN EL RENDIMIENTO ACADEMICO ESTUDIANTIL Y EK APRENDIZAJE SIGNIFICATIVO EN LOS OCTAVOS AÑOS DE EDUCACION BASICA DEL COLEGIO NACIONAL DE SEÑORITAS ''9 DE OCTUBRE'' DE LA CIUDAD DE GUAYAQUIL PERIODO LECTIVO 2007-2008. - ZOILA OCHOA SANCHEZ (2008)
DIDACTIC OF MATHEMATICS AND ITS IMPACT ON STUDENT ACADEMIC PERFORMANCE AND MEANINGFUL LEARNING IN THE EIGHTH YEARS OF BASIC EDUCATION OF THE NATIONAL SCHOOL FOR LADIES ''9 DE OCTOBRE'' OF THE CITY OF GUAYAQUIL SCHOOL PERIOD 2007-2008.